STRESS-INDUCED VARIABILITY IN LOCAL ANESTHESIA RESPONSE: EXPLORING IMPLICATIONS FOR DENTAL ANESTHETIC MANAGEMENT - Carmen Grierosu; Cozmin Mihai; Ionut Iulian Lungu; Gabriela Calin; Alina Stefanache; Mihaela Papusa Vasiliu; Gabriela Liliana Haliţchi; Daniela Ivona Tomiţa; Diana Mihaela Gheban; Codrin Paul Fuioaga; Norin Forna; Carmen Stadoleanu (Romanian Society of Oral Rehabilitation, 2024)
This article delves into the intricate relationship between stress, dental anxiety, and the variability in local anesthesia response, elucidating its impact on pain management and treatment outcomes in dentistry. Stress-induced physiological changes, exacerbated by anxiety, significantly influence pain perception and anesthesia efficacy, posing challenges for dental practitioners. Our work highlights the multifaceted effects of anxiety on anesthesia delivery, patient experiences, and treatment compliance, emphasizing the importance of tailored interventions to mitigate stress responses and optimize pain control. Strategies for managing dental fear and avoidance, including personalized approaches, technological innovations, and interdisciplinary collaboration, offer promising avenues for improving patient care and addressing the complex challenges associated with anxiety in the dental setting. By prioritizing patient-centered care and integrating psychological support into dental practice, practitioners can foster a supportive environment conducive to overcoming fear, enhancing treatment outcomes, and promoting oral health and well-being.